Energy Access Inequality in Indonesia: Socio-Economic Impact Analysis of the 2025 Pertamina Case on Fulfilling Citizens' Rights to Fair and Affordable Energy - Syakira, Firda; Fajri, Inayah; Artika, Revalina; Khairunnisa, Selvi Salsabillah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Energy inequality in Indonesia is exacerbated by corrupt practices, as in the